Antiferromagnetism in Ni‐Based Superconductors. Issue 4 (4th December 2021) - Zhou, Xiaorong; Zhang, Xiaowei; Yi, Jiabao; Qin, Peixin; Feng, Zexin; Jiang, Peiheng; Zhong, Zhicheng; Yan, Han; Wang, Xiaoning; Chen, Hongyu; Wu, Haojiang; Zhang, Xin; et al.
Abstract: Due to the lack of any magnetic order down to 1.7 K in the parent bulk compound NdNiO2, the recently discovered 9–15 K superconductivity in the infinite‐layer Nd0.8 Sr0.2 NiO2 thin films has provided an exciting playground for unearthing new superconductivity mechanisms. Herein, the successful synthesis of a series of superconducting Nd0.8 Sr0.2 NiO2 thin films ranging from 8 to 40 nm is reported. The large exchange bias effect is observed between the superconducting Nd0.8 Sr0.2 NiO2 films and a thin ferromagnetic layer, which suggests the existence of the antiferromagnetic order. Furthermore, the existence of the antiferromagnetic order is evidenced by X‐ray magnetic linear dichroism measurements. These experimental results are fundamentally critical for the current field. Abstract : The emerging Ni‐based infinite‐layer superconducting oxide thin films mark the birth of the Ni age of superconductivity, which may differ from well‐known high‐temperature superconducting cuprates and Fe‐based superconductors because no magnetic order is known in their bulk parent compounds. However, it has now been surprisingly discovered that long‐range antiferromagnetism coexists with superconductivity in infinite‐layer nickelate thin films.